PROFESSIONAL IDENTITY AND MEDICAL STUDENTS OF FOUNDATION UNIVERSITY MEDICAL COLLEGE - Bano, Uzma; Usman Mahboob; Tassadaq, Noreen (Journal of Postgraduate Medical Institute, 2021)
Objective: To measure the strength of professional identity across five years of MBBS course at Foundation University Medical College. Methodology: This cross-sectional study was conducted at Foundation University Medical College (FUMC) from January 2015 to September 2019. The study included medical students from first to final year MBBS through survey sampling. The questionnaire consisted of two components; PIS score measured the strength of Professional identity and PSIQ score measured the strength of PI as it is reflected in different professional activities. SPSS 20 was used for data analysis. Results: Study included 613 medical students whose mean age was 20.54±1.70 years and 26.4% were males. Professional identity starts forming right from the beginning of MBBS program and there was an overall increase in professional identity scores from first to final year; with mean PIS of 3.68 (i.e. close to “neutral”) in first year and 4.03 (i.e. into “agree” range) in final year. The increase in PIS score was statistically significant at two transitions; from 1st to 2nd and then from 3rd to 4th year. Clinical years (fourth and final year) were mainly responsible for most of the increase in PI and PSIQ scores. Conclusion: The professional identity scores increase over the five years of MBBS program. Clinical years significantly increase PI scores hence clinical clerkships should be introduced early through vertical integration.